Ateroprotective effects of Plinia cauliflora in. New Zealand rabbits: beyond the lipid-lowering effect - Cestari, Ana Paula; Gasparotto, Francielly Mourão; Kassuya, Cândida Aparecida Leite; Lacerda, Tauany Milan Ribeiro; Donadel, Guilherme; Moura, Catia Sari; Ceranto, Daniela Boleta; Jacomassi, Ezilda; Alberton, Odair; Tramontini, Salviano Belletini; Bertoncello, Luana Ale; Gasparotto Junior, Arquimedes; et al. (Frontiers in Pharmacology, 2024)
Introduction:Plinia cauliflora [Mart.] Kausel (Myrtaceae), popularly known as “jabuticaba,” is a fruit species native to Brazil. Despite extensive widespread usage, its antiatherosclerotic properties' impact remains unknown. Thus, the present study aimed to investigate the cardioprotective effects of a preparation obtained from the fruit peels of P. cauliflora (EEPC). Methods: Male New Zealand rabbits received a 1% cholesterol-supplemented diet for 60 days. On the thirtieth day, the animals were divided into five experimental groups and received, once a day, by the oral route, the EEPC (10, 30, and 100 mg/kg), simvastatin (2.5 mg/kg), or vehicle for 30 days. At the end of the experimental period, peripheral blood and arterial branch samples were collected. The levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), malondialdehyde (MDA), nitrotyrosine (NT), nitrite, interleukin 1 beta (IL-1b), interleukin 6 (IL-6), soluble inter-cellular adhesion molecule-1 (sICAM-1), and soluble vascular cell adhesion molecule-1 (sVCAM-1) levels were measured. Moreover, the catalase and superoxide dismutase levels were measured on the arterial samples. Histopathological analysis and arterial morphometry were also performed. Results and discussion: The oral administration of ESEG significantly lowered the levels of lipids in rabbits that were fed a CRD diet. This treatment also adjusted the protective system against oxidation in the arteries by decreasing the oxidation of lipids and proteins. Additionally, the levels of IL-1b, IL-6, sICAM-1, and sVCAM-1 in the bloodstream decreased significantly, and this was accompanied by a reduction of atherosclerotic lesions in all branches of the arteries. The findings suggest that EEPC may be a possible option for additional management of atherosclerosis.